2022
DOI: 10.1155/2022/7660118
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bioactive Compound Concentrated Growth Factor Ameliorates Fistula Healing of Anal Fistula in a Pig Model and Promotes Proliferation and Migration of Human Skin Fibroblasts via Regulating the MEK/ERK Pathway

Abstract: Recent evidence suggested that autologous concentrated growth factor (CGF), a new bioactive compound from autologous blood is used widely as an ingenious biomaterial in tissue regeneration with anti-inflammatory properties. This study investigated whether CGF could be involved in the treatment of fistula healing in the anal fistula. For this purpose, the porcine anal fistula model was conducted using the rubber band ligation method and collected pig autogenic CGF to treat the fistulas. CGF treatment promoted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…ERK1/2 constitutes an integral component of the MAPK family, and numerous studies have demonstrated that ERK1/2 signaling pathways are implicated in the regulation of airway inflammation and airway smooth muscle proliferation, and act as common signaling pathways ( Zhang et al, 2022 ; Goldklang et al, 2013 ). P65 could regulate the transcription of various genes involved in the immune response, including cytokines and inflammatory mediators ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 constitutes an integral component of the MAPK family, and numerous studies have demonstrated that ERK1/2 signaling pathways are implicated in the regulation of airway inflammation and airway smooth muscle proliferation, and act as common signaling pathways ( Zhang et al, 2022 ; Goldklang et al, 2013 ). P65 could regulate the transcription of various genes involved in the immune response, including cytokines and inflammatory mediators ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the ERK pathway regulates immunosuppression by reducing the Th17/Treg ratio. 10 , 11 , 12 Moreover, several small molecular compounds, such as sesamin, 13 2-(2-mercaptoethanol)-3-methyl-1,4-napthoquinone, 14 brain-derived neurotrophic factor, 15 and concentrated growth factor, 16 have been reported to activate the ERK pathway in the treatment of periodontitis and ADs such as UC. However, whether regulating the ERK pathway can enhance MSCT efficacy for AD treatment remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%